Dual-task performance under acute stress in female adolescents with borderline personality disorder - Kaess, Michael; Parzer, Peter; Koenig, Julian; Resch, Franz; Brunner, Romuald (European child & adolescent psychiatry, 2016)
Research to elucidate early alterations of higher cognitive processes in adolescents with BPD is rare. This study investigated differences in dual-task performance in adolescents with BPD during stress and non-stress conditions. The study sample comprised 30 female adolescents with BPD and 34 healthy controls. The impact of stress on dual-task performance was measured using a standardized stressor. Self-reports of distress and measures of heart rate (HR) were obtained to measure stress reactivity. There were no group differences in task performance. Under stress conditions, the performance on the auditory task decreased in both groups but without significant group differences. Healthy controls showed an increase of mean HR after stress induction compared to no change in the BPD group. The finding of attenuated HR response to acute stress in adolescent patients with BPD may contradict current theories that the affective hyperresponsivity in BPD is based on a biologically determined mechanism.
Gesehen am 08.02.2018